Navigating the nuclear tide: A comprehensive review of challenges, opportunities, and advances in managing marine contamination by radioactive contaminants - Adewale Giwa; Jamiu O. Eniola; Ayesha Bilal Salem; Aysha Ali Alshamsi; Kinda Amin Omar; Noor Saleh Alnuaimi; Sara Ghazwan Al-Fahad; Lulwa Ammar Rashed (Marine Pollution Bulletin, 2025)

Association between objectively assessed physical activity and kidney function among female agricultural workers in hot environments in Spain - Sarah Koch; Joren Buekers; Ana Espinosa; Juan Gómez-Salgado; Gabriel Pombo; Loes Werkman; Lourdes Arjona; Ali Al Rashed; Ben Caplin; Manolis Kogevinas; Francisco Brocal-Fernandez; Amin Oomatia; et al. (Environmental Research, 2025)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Protective influence of supplementary betaine against heat stress by regulating intestinal oxidative status and microbiota composition in broiler chickens - Ali R. Al Sulaiman; Ala M. Abudabos; Rashed A. Alhotan (International Journal of Biometeorology, 2024)

From source to house: unraveling the seasonal effect of water distribution system on drinking water quality of poultry farms under Egyptian environmental condition - Mohammed Abdelhameed Kamal; Rashed A. Alhotan; Ali R. Al Sulaiman; Elsayed Osman Hussein; Branislav Galik; Ahmed Ali Saleh (Environmental Science and Pollution Research, 2024)

Abdominoplasty Panniculus as a Source for Human Acellular Dermis: A Preliminary Report - Nayef Abdulrahman. Louri; Nigamananda Dey; Rashed N. AlHasan; Safa Hassan Abdulla; Mohamed Elsakka; Rasheeqa Gulreez; Abdulla Hassan Darwish; Balamuthu Kadalmani; Khalid Bin Ali Al Khalifa (Tissue Engineering and Regenerative Medicine, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Adsorptive removal of Cu(II) and Pb(II) onto mixed-waste activated carbon: kinetic, thermodynamic, and competitive studies and application to real wastewater samples - Zeid Abdullah ALOthman; Mohamed Abdelaty Habila; Nora H. Al-Shalan; Sulaiman M. Alfadul; Rahmat Ali; Ibrahim Gar Al alm Rashed; Bader Alfarhan (Arabian Journal of Geosciences, 2016)